Optimization and analysis of cutting parameters using cryogenic media in machining of high strength alloy steel - Tahir, Waseem; Jaffery, Husain; Ali, Liaqat; Khan, Mushtaq; Butt, Shahid; Jaffery, Mehdi (Cranfield University Press, 2013)
In this research, liquid Argon is used as a cryogenic media to optimize the cutting parameters for evaluation of tool flank wear width of Tungsten Carbide Insert (CNMG 120404-WF 4215) while turning high strength alloy steel. Robust design concept of Taguchi L9 (34) method is applied to determine the optimum conditions. This analysis revealed is revealed that cryogenic impact is more significant in reduction of the tool flank wear.
Keywords: turning; liquid argon; flank wear